Development status and formula design of food for elders - QIANG Wan-li; ZHANG Lian-hui; YING Xin; LI Hui; HUAN Mei-li; LI Jing (Liang you shipin ke-ji, 2020)
Global aging is a major trend of social development and it’s also a major challenge that people face.Due to the physiological factors such as organ dysfunction，cell and muscle attenuation，anabolic metabolism less than catabolic metabolism，the elderly are easier to have diet dysfunction，muscular attenuation，digestion，malnutrition and other health problems.Through the investigation，it was found that products for elders in Chinese market were limited and the nutrients were not comprehensive，moreover，most of the products could not meet the dietary nutrition needed for elderly consumers.This review investigated the existing problems and challenges of the food for elders in the current market based on the current health status of elders in China.This review further summarized formula design and key technology of food for elders，in order to provide technical support and advice for designing-foods that could meet the nutritional needs of aging diet.